Sexually transmitted diseases in a specialized STD healthcare center: epidemiology and demographic profile from january 1999 to december 2009 - Luiz Jorge Fagundes; Elso Elias Vieira Junior; Ana Carolina Marteline Cavalcante Moysés; Fernão Dias de Lima; Fátima Regina Borges de Morais; Natalina Lima Vizinho (Sociedade Brasileira de Dermatologia, 2013)
BACKGROUND: Sexually Transmitted Diseases are still considered a serious public health problem in Brazil and worldwide.OBJECTIVE: To examine Sexually Transmitted Diseases prevalence and the sickness impact profile of STDs in a reference health center specializing in the treatment of Sexually Transmitted Diseases.METHOD: We collected epidemiological, demographic, clinical and laboratory data from the medical records and interviews of 4,128 patients who had attended the center from January 1999 to December 2009.RESULTS: Male patients outnumbered (76%) females (24%), Caucasians outnumbered (74.3%) those of mixed race (14.8%), blacks (10.8%) and Asians (0.1%). STD occurrence was higher in the 20-29 age group (46.2%) This population included 34.7% high school graduates, 8.7% college graduates and 0.8% illiterates. As for affective-sexual orientation, 86.5% were heterosexual, 7.8% homosexual and 5.5% bisexual. Regarding patients' sexual practices over the previous 30 days, 67.7% reported sexual intercourse with one person, 8.6% had had sex with two persons and 3.9%, with three or more people. The highest incidence of STD was condyloma acuminata, affecting 29.4% of all the patients, genital candidiasis 14.2%, and genital herpes 10.6%. Of the 44.3% who submitted to serologic testing for HIV detection 5% were positive, with a ratio of 6.8 males to 1 female.CONCLUSIONS:STD prevalence remains high in Brazil and it is necessary to invest in early detection, prevention and treatment.